2005
DOI: 10.1111/j.1532-5415.2005.53512.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Is a Better Predictor of Impaired Immunity than Chronological Age in Older Adults

Abstract: This study demonstrates that the level of comorbidity correlates with the magnitude of immune response in older adults and suggests that the CIRS could be used to determine the magnitude of impaired immunity in older adults with different specific illnesses and different levels of severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 20 publications
4
38
0
2
Order By: Relevance
“…Of the non-modifiable patient factors, senescence has consistently been shown to be associated with lower ln yield 18,20,22,[24][25][26] . That observation might reflect decreased immune response with aging 27 and comorbidity 28 . Right-sided tumours are also known to be associated with higher ln counts [18][19][20][21][22][24][25][26]29 , likely a result of a larger mesenteric surface and the presence of multiple vascular trunks 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the non-modifiable patient factors, senescence has consistently been shown to be associated with lower ln yield 18,20,22,[24][25][26] . That observation might reflect decreased immune response with aging 27 and comorbidity 28 . Right-sided tumours are also known to be associated with higher ln counts [18][19][20][21][22][24][25][26]29 , likely a result of a larger mesenteric surface and the presence of multiple vascular trunks 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Galon et al 41 coined the term "immune contexture" to describe the effect of the local host immune reaction in crc. There is a negative association between senescence and decreased nodal count 27 , and possibly a stronger association between comorbidity and diminished immunity 28 ; also, patients with crcs that genomically harbour microsatellite instability have a propensity for right-sided malignancies 42 , higher ln yields 43 , and better overall prognosis 44 . Given those findings, it is entirely plausible that ln yield is the surrogate marker for an immune response that reflects inherent prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…One major difficulty here is to dissect the role of aging in the decreased immune response compared to the role of chronic disease, itself causing immune alterations exacerbating other chronic diseases (Castle et al 2005(Castle et al , 2007. The question is whether a high chronic disease burden leads to impaired immunity or the impaired immunity leads to high chronic disease burden or perhaps more likely, interactions in both directions.…”
Section: Frailty and Age-related Diseasesmentioning
confidence: 99%
“…Other studies have shown that some clinical conditions often found in the elderly, such as cardiovascular disease and other chronic conditions, may also contribute to a decreased immune response to influenza vaccine. In addition, influenza is caused by a viral agent with many different serotypes, which render it a highly prevalent disease; that can also affect the rate of vaccine protection [23][24][25] . To better discuss these data it is very important to take into account the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%